MENAFSIR MASYARAKAT ADAT HATUHAHA AMARIMA DENGAN PENDEKATAN HERMENEUTIKA PAUL RICOEUR DAN SIGNIFIKANSINYA UNTUK HIDUP DALAM PERSAUDARAAN - A. Uhi, Jannes (HUMANIKA, 2014)
Abstract Hermeneutics is no longer focused on the written text, but has grown and that concerns to the spoken texts. The development of hermeneutics of interpretation of written text into spoken text is intended to express the meaning behind human actions are not mentioned in the article. Phenomenology indigenous of Hatuhaha Amarima with the culture’s through meaningful when interpreted with Paul Ricoeur's hermeneutic approach. Deepest meaning of phenomenology indigenous of Hatuhaha Amarima useful in establishing a life together in religious differences. Religious differences to provide awareness for indigenous peoples to survive in there al brotherhood became everyone's expectations. Keywords: hermeneutics, Hatuhaha Amarima, brotherhood